“They know exactly with whom to speak German and with whom English”: Grade-R children's language and literacy practices in the context of the linguistic and literacy repertoires and ideologies of four Cape Town bilingual families with German as a heritage language - Kraus, Isabel Marissa (School of Education, 2025)
South Africa is a country of 11 official languages, with a majority of the population speaking at least two languages. Bilingual/multilingual upbringing is the reality of most South African children, and the transfer and maintenance of heritage languages is an important topic in the field of language and literacy studies. A range of different factors come into play in bilingual and multilingual parents' decisions about how to raise their children concerning languages. The field of family language policy (FLP) shows how language ideologies are involved as to how languages are managed, learned, and negotiated within individual families. Furthermore, families engage in a wide range of language and literacy practices in their homes, which are shaped by the FLP and their language and literacy ideologies. This case study, which draws on linguistic ethnography, focuses on the language and emergent literacy practices of four grade R learners in their bilingual/multilingual homes where German is the heritage language, in Cape Town, South Africa. The data was collected through interviews with the parents, observations of the children in their homes, and the collection of literacy artefacts. The observations focused on the language used during family interactions, noting the conscious and unconscious choices around family language policies, as well as emergent literacy practices and uses of digital technologies. Findings show that family language policy and the language ideologies of the parents influence the language and literacy practices of their children. Translanguaging (Garcia 2009) was used in all families, the children showed a variety of linguistic repertoires (Busch 2012), and they were able to engage in meaningful conversations in different languages. The heritage language process was influenced by the parents' own bilingual/multilingual upbringing, and the parents put a lot of value on the acquisition and maintenance of the heritage language, German. Emergent literacy practices took place in different languages and the children were able to draw on their linguistic repertoires to make meaning. The language and literacy ideologies of the school (in our case, a kindergarten with German as the language of teaching and learning) influence the emergent literacy practices at home, and the parents followed the lead of the school not to teach their children how to read and write at home. The children's language identity was shaped by their family language policy and their parents' reasoning to uphold their heritage language. Language ideologies play an important role in the negotiation of FLP and children are making their own language choices by using translanguaging to communicate. They, therefore, have an agentic role in their language-learning process and should be seen as co-constructing the FLP.